Formation and Evolution of the Large‐Scale Magnetic Fields in Venus' Ionosphere: Results From a Three Dimensional Global Multispecies MHD Model. Issue 11 (1st June 2020) - Ma, Yingjuan; Toth, Gabor; Nagy, Andrew; Luhmann, Janet; Russell, Christopher
Abstract: Large‐scale magnetic fields have been observed in Venus' ionosphere by both the Pioneer Venus Orbiter (PVO) and Venus Express spacecraft. In this study, we examine the formation and evolution of the large‐scale magnetic field in the Venus ionosphere using a sophisticated global multispecies Magnetohydrodynamics (MHD) model that has been developed for Venus (Ma et al., 2013, https://doi.org/10.1029/2012JA018265 ). A time‐dependent model run is performed under varying solar wind dynamic pressure. Based on model results, we find that (1) the initial response of the induced magnetosphere is fast (~min), (2) a large‐scale magnetic field gradually forms in the ionosphere when the solar wind dynamic pressure suddenly exceeds the ionospheric thermal pressure, (3) both the penetration and decay of the large‐scale magnetic field in the ionosphere are slow (~hr), and (4) the ion escape rate has a nonlinear response to the change of solar wind dynamic pressure. Plain language Summary: Large‐scale magnetic fields have been observed at Venus' ionosphere by previous Venus missions. In this study, we examine the formation and evolution of the large‐scale magnetic field in the Venus ionosphere using a sophisticated global model. A time‐dependent model run is performed under varying solar wind dynamic pressure (density). Model results show that the outside interaction region responds quickly (~min) to the solar wind variation, while the response time of the ionosphere is long (~hr). We also found that the ion escape rate has a nonlinear response to the change of solar wind dynamic pressure. Key Points: The global MHD model self‐consistently reproduces the formation and evolution of the large‐scale magnetic fields in the Venus ionosphere Model results show that it takes quite long time (~hr) for the magnetic field to penetrate into and decay in the ionosphere The large‐scale magnetic fields in the ionosphere act as an additional obstacle to the solar wind